Middle Permian diversity of large herbivores: taxonomic revision of the titanosuchidae (therapsida, dinocephalia) of the Karoo basin, South Africa - Jirah, Sifelani (My University, 2022)
Titanosuchidae are a goup of derived herbivorous long snouted dinocephalians currently only known from the South African Karoo Supergroup. Taxonomic revision of the titanosuchids, for the first time accompanied by detailed anatomical descriptions and illustrations of representative cranial and postcranial material, enabled recognition of only two genera each represented by a single species out of nine previously recognized species. These are Titanosuchus ferox and Jonkeria truculenta. Jonkeria vanderbyli, Jonkeria ingens, Jonkeria haughtoni, Jonkeria parva, Jonkeria rossouwi and Jonkeria boonstrai are here, synonymized with Jonkeria truculenta. The species Jonkeria koupensis is a nomen dubium only identified as Titanosuchid indet. Cranial characters, which modify during ontogenetic development, were, recognized for Jonkeria, and for the first time an ontogenetic growth series is, presented for this species. This research has for the first time produced a phylogenetic analysis of the two titanosuchid taxa with their deuterosaurid, estemmenosuchid, anteosaurid, styracocephalid and tapinocephalid counterparts confirming the sister group relationship between Styracocephalidae, Estemmenosuchidae, Titanosuchidae and Tapinocephalidae. This phylogenetic analysis manifests a long ghost lineage extending over most of the Guadalupian. The first extensive stratigraphic analysis of the Titanosuchidae shows that the South African Karoo Supergroup hosts both genera in the upper levels of the Abrahamskraal Formation (Moordenaars Member) with a single specimen (Titanosuchid indet) recovered in the lower levels of the overlying Poortjie Member of the Teekloof Formation. The absence of titanosuchids in the Karelskraal Member of the Abrahamskraal Formation and their reappearance in the lower Poortjie could be a case of a “Lazarus taxon”. This gap in the stratigraphic range of this taxon iv (range gap), as well as the long ghost lineage, will hopefully be filled in future by intensive targeted collecting in the relevant stratigraphic intervals.
A thesis submitted in fulfilment of the academic requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Geoscience, University of the Witwatersrand, Johannesburg, 2022